Proceedings of the 44th IEEE Conference on Decision and Control
DOI: 10.1109/cdc.2005.1582653
|View full text |Cite
|
Sign up to set email alerts
|

On hardware-in-the-loop simulation

Abstract: Hardware-in-the-loop simulation is a well established technique used in design and evaluation of control systems. The purpose of this paper is twofold. First it aims to identify research questions related to the design of hardware-in-the-loop simulation. Second it suggests possible measures of assessing the simulation fidelity of hardware-the-loop simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
4

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 12 publications
0
63
0
4
Order By: Relevance
“…However, a simplified recursive procedure for predicting the process free response is now described. To obtain this output predictor from Equation (22), first multiply throughout by ∆ to give A(z)∆Y(z) = B(z)∆U(z) + W(z). At discrete time step k, it can be observed that the expected future values of the random disturbance term w(k + i) = 0 for all i > 0, and since the free response is required, it can also be assumed that the future controls ∆u(k) = 0 and ∆u(k + 1) = 0.…”
Section: Optimal Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a simplified recursive procedure for predicting the process free response is now described. To obtain this output predictor from Equation (22), first multiply throughout by ∆ to give A(z)∆Y(z) = B(z)∆U(z) + W(z). At discrete time step k, it can be observed that the expected future values of the random disturbance term w(k + i) = 0 for all i > 0, and since the free response is required, it can also be assumed that the future controls ∆u(k) = 0 and ∆u(k + 1) = 0.…”
Section: Optimal Predictionsmentioning
confidence: 99%
“…HIL simulation provides an effective technique for designing and testing of real-time and embedded control systems [20][21][22][23][24][25]. HIL testing is used to lower total costs, shorten development cycles, and improve functional performance of real-time and embedded control systems.…”
Section: Hil Testing Facilitymentioning
confidence: 99%
“…Uses can also be found in the control of electrical machines and in robotics applications (induction machine drives [28,29] and motion control [30,31]). More recently, reconfigurable devices have been increasingly finding applications as means for implementing hardware-in-the-loop platforms [32,33] for debugging purposes principally but increasingly as a means to emulate subcomponents of larger systems. …”
Section: Trends In the Use Of Fpgas For Implementing Iedsmentioning
confidence: 99%
“…In this paper, we seek to explore the impact of applying "Nolte C" and SBS on another realistic case study; that is the distributed control of a CarboNitriding heat treatment furnace system built using "hardware-in-the-loop" (HIL) testing method [29,30]. HIL has been extensively used in embedded systems development and refinement processes, particularly for automotive applications (see, for example, [31][32][33][34][35][36][37]).…”
Section: Introductionmentioning
confidence: 99%